Preferences for HIV Testing Services and HIV Self-Testing Distribution Among Migrant Gay, Bisexual, and Other Men Who Have Sex With Men in Australia - Zhang, Ye; Wiseman, Virginia; Applegate, Tanya L.; Lourenco, Richard De Abreu; Street, Deborah J.; Smith, Kirsty; Jamil, Muhammad S.; Terris-Prestholt, Fern; Fairley, Christopher K.; McNulty, Anna; Hynes, Adam; Johnson, Karl; et al. (Frontiers in Medicine, 2022)
Background In Australia, undiagnosed HIV rates are much higher among migrant gay, bisexual, or other men who have sex with men (GBMSM) than Australian-born GBMSM. HIV self-testing is a promising tool to overcome barriers to HIV testing and improve HIV testing uptake among migrant GBMSM. We compared the preferences for HIV testing services, including HIV self-testing, among migrant and Australian-born GBMSM. Methods Preferences were assessed via two discrete choice experiments (DCEs). Participants were recruited between December 2017 and January 2018 using online and offline advertising and randomly assigned to complete one of two online DCE surveys. Migrant GBMSM were classified as being born in a country with a reciprocal healthcare agreement (RHCA) with Australia (providing free or subsided health care) or not. Latent class analysis and mixed logit models were used to explore heterogeneity in preferences. Findings We recruited 1,606 GBMSM, including 583 migrant men of whom 419 (72%) were born in non-RHCA countries. Most participants preferred a free or cheap oral test with higher accuracy and a shorter window period to facilitate early detection of infections. Cost was more important for men born in non-RHCA countries than for men from RHCA countries or Australia. All groups preferred accessing kits through online distributers or off the shelf purchasing from pharmacies. Men born in RHCA countries least preferred accessing HIV self-testing kits from a medical clinic, while more than half of men from non-RHCA countries most preferred sourcing kits from a clinic. Sex-on-premises venues were the least preferred location to access test kits among all groups. In addition, two latent class analyses explored heterogeneity in preferences among men from non-RHCA countries and we found four latent classes for HIV testing services and two latent classes for HIVST distribution. Interpretation Our findings emphasise the need for high-performing and low-cost HIV self-testing kits that are accessible from a variety of distribution points as a component of Australia's HIV response, especially for those who do not have access to free or subsidised health care in Australia.